Design Adaptive controller and learning controller to control the pacemaker: تصميم متحكم تكيفي ومتحكم متعلم للتحكم بناظم الخطى القلبي - Eliatha Nasr Alden Alebrahem, Jomana Mahmoud Diab, Feras Mohammad Zoreka (Journal of engineering sciences and information technology, 2020)
Pacemakers play a vital role in the management of electrical disorders of the heart, as having a controller that presents a signal that generates a correct heart rate without delay or overshoot is important, to provide better quality and long-term patient’s life. Many advances in pacemaker control technology have been achieved, making today’s pacemakers capable of correcting many electrical heart abnormalities. In this paper, a fuzzy model reference learning control was designed to control the pacemaker, and compared with a controller adopts the adaptive mechanism instead of the learning mechanism, in order to confirm the importance of learning in the controller. The controller automatically controls the heart rate (Heart Rate: HR) to prevent it from falling under a reference value and makes it track preset signal accurately. The learning controller achieved better performance than the adaptive controller and the learning controller achieved when comparing with the similar intelligent ones that proposed to control pacemaker the required response with a small settling time 0.9s, and minimized the overshoot at start-up operation where overshoot was 0.2%